HYBRID LEARNING IN SELECTED JUNIOR HIGH SCHOOL: IS IT A SOLUTION FOR EFL LEARNING LOSS? - Ima Masofa; Irwan Sumarsono; Abu Fanani (Undiksha Press, 2023)
The use of hybrid learning in junior high school English as a Foreign Language classes can be a combination of teaching and learning strategies and a remedy for learning loss. Since MO365 is an application for the online final tests in 2020 without hybrid learning and in 2021 with hybrid learning, where the teacher uses hybrid learning that she uses online and limited offline learning, this paper aims to explore the implementation of hybrid learning in English final tests. It focuses on the similarities and differences in responses of two final tests in junior high school in second grade using MO365. The study's findings can be summarized as follows; (1) To get different results on the two final online English tests in MO365, which are 68, 4 without hybrid learning, and 90.1, with hybrid learning. (2) In 2020 without hybrid learning, eighth-grade students experience learning loss due to the Covid 19 Pandemic, whereas students in the same grade in 2021 with hybrid learning achieve better scores 90.1 than those in the same grade in 2020 without hybrid learning 68.4 because their school only offers a small amount of offline learning. This study can be utilized as a guide and a solution by teachers to enhance hybrid learning, which will help students learn the subject more easily and more conveniently by integrating online and offline learning. Keywords: hybrid learning, final test, MO365, learning loss, pandemic